Gamifikasi Dalam Pembelajaran Di Sekolah Dasar - Wasilatul Ibad (IAI Al Khoziny Buduran Sidoarjo, 2024)
This research aims to investigate the impact of gamification on motivation and Learning outcome. The research is based on observed learning conducted on students who are less motivated to be active in learning Islamic education subjects in elementary schools. The gamification design was chosen based on many sources stating that gamification can help children achieve learning goals. The subjects of this research are students of Bator 2 Elementary School. The object of the research is baamboozle as a gamification. This research is descriptive-quantitative. The sample for this research was 40 students. The main finding in this research is that there is an impact of gamification on motivation. It is evident from the results of hypothesis testing that r count > r table (0.507 > 0.312), so H1 is accepted and H0 is rejected. There is no impact of gamification on Learning outcome. It is evident from the hypothesis test results that r count ˂ r table (0.136 ˂ 0.312), so H1 is rejected and H0 is accepted. From the results of this analysis, it can be concluded that gamification has a sufficient impact on motivation but has no impact on Learning outcome.